(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
تمت هذه الدراسة لتحديد التغيرات الموسمية في أعداد عثة الزيتون Prays oleae Bern ( Lep: Yponomeutidae ) للجيلين الزهري و الورقي وتأثيرها في المتطفلات المرافقة لها في بعض مناطق محافظة ادلب (كفرتخاريم والجانودية) 2008 و 2009. كان تعداد فراشات عثة الزيتون في المصائد الفرمونية عام 2008 منخفض حيث بلغ المعدل التراكمي للجيلين الزهري والورقي في كفرتخاريم 90 و89 حشرة/مصيدة على التوالي، وفي الجانودية 70 و77 حشرة/مصيدة على التوالي. بينما كانت قيمة هذا التعداد مرتفعة جداً في عام 2009 وبفروق معنوية عالية (p<0.001) حيث بلغ المعدل التراكمي للجيلين الزهري والورقي في كفرتخاريم 1321 و1015 حشرة/مصيدة على التوالي وفي الجانودية 901 و788 حشرة/مصيدة على التوالي. أثر تعداد العائل في نسب التطفل بحيث لم تتمكن المتطفلات من السيطرة على مجتمع الآفة لعام 2009، فقد بلغت نسبة التطفل الكلية عام 2008 للجيلين الزهري و الورقي في كفرتخاريم 30.5% و 34.7% على التوالي وفي الجانودية 29.9% و31.5% على التوالي. بينما سجلت تلك النسبة في عام 2009 للجيل الزهري و الورقي 16.8% و 20.1% على التوالي في كفرتخاريم وفي الجانودية 14.6% و 18.2% على التوالي. اختلفت نسبة التطفل باختلاف سنوات الدراسة وبمعنوية عالية (L.S.D= 3.88) بينما لم يكن هنالك اختلافات بين مواقع الدراسة. This study has been carried out to determine the seasonal variations in the population of olive moth Prays oleae Bern (Lep: Yponomeutidae) Phyllophagous & Anthophagous generations and its impact on the accompanied parasitoids in some regions of Idleb governorate Kafertakareem & Janodea 2008 & 2009. The number of olive moth in pheromone traps was low in 2008 for the two generations Anthophagous & Phyllophagous, whereas it was in Kafertakareem (90 & 89 insect/trap) respectively, and in Janodea (70 & 77 insect/trap) respectively. In 2009, there were significant differences in comparison with 2008 (p<0.001). The accumulation account in Kafertakareem for the two generations was (1321 &1015 insect/trap) respectively, and in Janodea (901 & 788 insect/trap) respectively. Host population affected parasitism percentage as the parasitoids didn’t control the pest community in 2009 where the total parasitism percentage in 2008 for two generations Anthophagous & Phyllophagous in Kafertakareem were (30.5% & 34.7%) respectively, and in Janodea (29.9% & 31.5%) respectively. While in 2009, it was (20.1% & 16.8%) respectively, in Kafertakareem and (18.2% & 14.6%) respectively in Janodea. However, variations of years had significant effect in parasitism percentage at (L.S.D= 3.88), while the sites did not have any effects.